DYNAMICS OF DETECTED FIRE FACTORS IN CLOSED COMPARTMENT: COMPUTER SIMULATION - V. V. Nevdakh (Приборы и методы измерений, 2015)
Computer simulation of the initial fire stages in closed compartment with the volume of ≈ 60 m3 and with a burner on a floor and 2 m above floor have been carried using FDS software. Fires with different t 2 –power low heat release rates have been modeled. Fires which growth times to reach 1055 kW were 100 s and 500 s have been considered as fast and slow fires respectively. Dynamics of heat release rates and detected fire factors such as spatial distributions of air temperature, smoke obscuration and variations of indoor pressure have been studied. It has been obtained that dynamics of heat release rates of the initial fire stages in closed compartment consists of two stages. During the first stage the heat release rate is proportional to mass burning rate and flaming occurs only above a burner. At the second stage dynamics of heat release rates has a form of irregular in amplitude and duration pulsations, which are caused by self-ignition in the smoke layer. The compartment air volume may be layered with respect to the height and every layer has its oven temperature, smoke obscuration, self-ignition areas have been shown. The layer thickness, gradients of temperature and obscuration depend on a fire growth rate and on a burner height above floor have been concluded. The spatial distributions of air temperature and pressure variation have the opposite gradients on a height have been obtained. Maximal pressure variation and its gradient occurs under the fast fire with a burner on a floor have been obtained too.